Determining Implied Instructions in Joshua 3 and 7: A Contextual Hermeneutic of Consecration Activities - Allen Hamlin Jr. (Tyndale Bulletin, 2024)
Commands directed toward individuals and groups to consecrate themselves occur with highest concentration in the Pentateuch. However, there is a variety of instructions which occasionally accompany these mandates, leading to a lack of clarity about the process of consecration and how those commands are fulfilled. This ambiguity is especially notable in encountering very blanket commands as in the narrative texts of Joshua 3:5 and 7:13, where no additional ritual instructions are provided alongside the consecration imperatives nor revealed in the ensuing stories. By examining selected Pentateuchal instances of consecration (especially of persons), evaluating the links between passages and the paradigmatic nature of certain occurrences, and considering the broader ancient West Asian context of consecration activities, this paper will offer a hermeneutic to facilitate determining what instructions, if any, may be implied when the commands to consecrate oneself or others are issued in a narrative context.